Answers

2014-07-13T21:11:09+05:30
6x2 – 3 – 7x
Factorize the equation  
Compare the equation with ax2  + bx  + c  = 0
We geta = 6 ,b=-7 c= -3
To factorize the value we have to find two value which sum is equal to  b =-7
product is a*c  = 6*-3=-182 and -9 are required values which sum is 2 – 9     = - 7
product is 2 * - 9= - 18
So we can write middle term as -7x      = 2x – 9x 
We get 2x (3x +1) -3(3x +1) = 0(3x+1)(2x-3)   = 03x+1 = 0 , 2x-3 = 0
Solve for first zero3x = - 1x  = -1/3
Solve for second zero2x-3 = 02x    = 3X      =  3/2   
Plug the values of a , b and c we get
Sum  of zeros -b/a = -(-7/6)= 7/6
Product of zero c/a = -3/6= -1/2
hence we have verified the relationship   

0